Determining performance characteristics of jet water-gas ejectors for an opening in a vertical fencing structure - Hrynchak, Serhii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is jet water-gas ejectors (JWGEs) in the system for ensuring fire safety of ships. The problem that was solved: in the event of a fire, in the shortest possible time, a high temperature rises in the area of ​​the exit from the ship's emergency room and a large amount of smoke spreads throughout the ship's premises. These factors require immediate sealing of the emergency room, which limits the immediate access of emergency teams to the interior. Installation of a local air support system based on JWGE in the doorway could make it possible to shield thermal energy and localize smoke gases in the emergency room without sealing it to ensure prompt access of emergency teams. The main results that were achieved relate to the adequacy of theoretical studies on the processes of localization of flue gases in the emergency room without its sealing confirmed by the experimental method. The investigated problem was solved by optimizing processes: the intensity of smoke emission from the working characteristics of jet water-gas ejectors; the rate of change of the natural indicator of the weakening of the environment at the start of JWGE system; speed of reaching the required temperature from the time in the adjacent room. Special feature of the results was the formation of an air curtain, obtained by the selection of a part of high-temperature flue gases into the JWGE housing, their heat and mass exchange treatment and output back into the flow. This created conditions under which thermal energy shielding occurs with a fairly high efficiency of 85–88 %. And it was also established that the decrease in the intensity of gas exchange through the open hole, in which the JWGE works, occurs already at the 0.3 MPa regime in the fire pipeline. The scope and conditions of practical use of the reported results are shipbuilding and ship fire safety design